The future of forests and orangutans (Pongo abelii) in Sumatra: predicting impacts of oil palm plantations, road construction, and mechanisms for reducing carbon emissions from deforestation - Gaveau, D.L.A.; Wich, S.; Epting, J.; Juhn, D.; Kanninen, M.; Leader-Williams, N. (2009)
Payments for reduced carbon emissions from deforestation (RED) are now attracting attention as a way to halt tropical deforestation. Northern Sumatra comprises an area of 65 000 km2 that is both the site of Indonesia’s first planned RED initiative, and the stronghold of 92% of remaining Sumatran orangutans. Under current plans, this RED initiative will be implemented in a defined geographic area, essentially a newly established, 7500 km2 protected area (PA) comprising mostly upland forest, where guards will be recruited to enforce forest protection. Meanwhile, new roads are currently under construction, while companies are converting lowland forests into oil palm plantations. This case study predicts the effectiveness of RED in reducing deforestation and conserving orangutans for two distinct scenarios: the current plan of implementing RED within the specific boundary of a new upland PA, and an alternative scenario of implementing RED across landscapes outside PAs. Our satellite-based spatially explicit deforestation model predicts that 1313 km2 of forest would be saved from deforestation by 2030, while forest cover present in 2006 would shrink by 22% (7913 km2) across landscapes outside PAs if RED were only to be implemented in the upland PA. Meanwhile, orangutan habitat would reduce by 16% (1137 km2), resulting in the conservative loss of 1384 orangutans, or 25% of the current total population with or without RED intervention. By contrast, an estimated 7824 km2 of forest could be saved from deforestation, with maximum benefit for orangutan conservation, if RED were to be implemented across all remaining forest landscapes outside PAs. Here, RED payments would compensate land users for their opportunity costs in not converting unprotected forests into oil palm, while the construction of new roads to service the marketing of oil palm would be halted. Our predictions suggest that Indonesia’s first RED initiative in an upland PA may not significantly reduce deforestation in northern Sumatra and would have little impact on orangutan conservation because a large amount of forest inside the project area is protected de facto by being inaccessible, while lowland forests will remain exposed to the combined expansion of high-revenue plantations and road networks. In contrast, RED would be more effective in terms of its conservation impact if payments were extended to all remaining carbon-rich tropical forests, including lowland peat swamp forests, the preferred habitat for dense populations of orangutans, and if the construction of new roads was halted. © 2009 IOP Publishing Ltd